ChemInform Abstract: Catalyst‐ and Solvent‐Free, Pot, Atom and Step Economic Synthesis of Tetrahydroquinazolines by an Aza‐Diels—Alder Reaction Strategy. Issue 32 (24th July 2014) - Bhuyan, Debajyoti; Sarma, Rupam; Dommaraju, Yuvaraj; Prajapati, Dipak
Abstract The microwave‐assisted aza‐Diels—Alder reaction of 2‐naphthylamine (I) with aryl aldehydes (II) and ammonium acetate leads to desired bis‐aryl tetrahydroquinazolines (III) in good yields.